PENGARUH LATIHAN COMPASS DRILLTERHADAP KELINCAHAN PADA SISWA PUTRA KELAS 1 EKSTRAKURIKULER SEPAKBOLA SMK TELKOM PEKANBARU - Fernando, Fiezy Fernando; Agust, Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT :This research was conducted in order to know is there any impact in Compass Drill exercise to Agility to ward the first year male students football club SMK Telkom Pekanbaru to get an expected result when playing football. This research is an Experimental while the sample is 20 students who is join the football club of the first grade. The isnstrument of the research is using Illiois Agility Run Test which aims to measure the students agility. The data was analyzed using to examine the impact of Compass Drill to ward agility. After that, the datais processedwith statistics, to testthe normality ofthetestata significant level0,05a lilifors. The hypothesis isthe effectof exerciseCompass DrillAgility.Based ont test analysisproducesThitungof 7,14andTtabel 1,792, meansTaccont>Ttabel. Based on the T-Testanalysis the mean ofPree-test 19,22 and the mean of Post-test is 17,99 which shows the data is normal. It mean, Ha is accepted, there is impacy of Compass Drill to ward Agility the first year male students football club SMK Telkom Pekanbaru. Keywords: Compass Drill, Agility